PENGEMBANGAN METODE FERMENTASI BIJI KOPI DENGAN MENGUNAKAN INKUBATOR TERKONTROL FUZZY LOGIC DAN MONITORING IOT - Sunandar Djasba; Abdul Waris; Junaedi Muhidong (Ensiklopedia of Journal, 2023)
The purpose of this study was to determine the quality of coffee bean basket yields with a fuzzy logic controlled incubator. The method in this research is experimentation by packing coffee beans in an incubator using a stirrer and without a stirrer. Fermentation was carried out for 12 hours at 40oC with two repetitions. The amount of fermented coffee was 3.5 kg for each treatment. Stages of hardening: coffee peeling, washing, weighing, and measuring the pH of the air in the stirrer container. After the measurement, the pH of the water was measured, the color test, the water content of the coffee beans, the pH of the coffee powder, and the total acid. The results obtained from this study are in the form of a tool that is tuned using an IoT-based fuzzy logic control system that can perform a temperature control system in the incubator room automatically based on a temperature set point of 40oC, a fan control device that functions to even out the temperature of the incubator room, and the temperature and power parameters used are monitored through the thingspeak application. The rules used to brew coffee beans are quite good based on that there is no overshoot, the steady state error is still in the range of 2-5, the settling time is quite short, stable and the energy used is relatively small during the coffee bean roasting process. Indicators of the quality of coffee beans produced from settlement according to SNI values include the amount of water content of coffee beans using a stirrer, which is 11.04% and without a stirrer, 11.18%, the color of the coffee beans has a chroma/color intensity (L*) value of 33.02 which is close to the biofermentor's L value of 31.71, the pH of coffee grounds steeping is 4.3 and the total acid steeping powder is 0.53%.